Productivity Gaps and Global Systematic Risk Exposure: Pricing Country-Industry Portfolios - Anand, Punit; Balvers, Ronald J. (2020)
Shocks transmitted from productivity leaders to lagging economies are systematic sources of risk. Global technology and knowledge diffusion leads to predictable patterns in productivity dynamics across countries and industries. Technology gaps determine the level of exposure to the systematic productivity shocks. Firms in a country-industry with larger technology gaps relative to the world leader are more dependent on the leader’s innovations compared to their own productivity improvements. They thus have higher loadings on the leader productivity shocks and higher average stock returns. For OECD panel data, a country-industry’s technology gap significantly predicts the stock returns of the country-industry: holding the quintile of country-industry portfolios with the largest gaps and shorting the quintile with the smallest gaps generates annual returns of 9.8% (6.7% after risk adjustment with standard factors). A factor representing the technological productivity gap explains country-industry portfolio returns substantially better than standard factor models. Loadings on leader-country productivity shocks have substantial correlation with technology gaps, and leader productivity shocks are more important for stock returns than idiosyncratic productivity shocks. These findings support that the technology gaps and associated higher average returns are indeed linked to systematic risk.
Keywords: International Equity Returns; OECD Countries; Production-Based Asset Pricing; Productivity Gap; Technology Diffusion; Total Factor Productivity; dept.fin

Short selling prior to going concern disclosures - Huang, Jian; Wang, Lei; Yu, Han; Zhang, Zhen (Accounting and Business Research, 2020)
We provide insights into how the market processes going concern audit opinions based on the trading of some well-documented sophisticated investors–short sellers. We find that abnormal short selling increases significantly upon impending going concern disclosures. While prior literature attributed much of short selling around some corporate events to private information, we find evidence that pre-going-concern announcement short selling reflects both privately informed trading and processing of public information by short sellers. Further, a negative relation between pre-announcement short selling and post-announcement short-term stock returns exists for stocks with less short sale constraints. We also find moderate evidence associating short selling with subsequent bankruptcy to some extent. Overall, these results suggest that short sellers front run going concern announcements based on private information and fundamentals, although trading constraints prevent them fully impounding the severity of negative information in the short run, providing a partial explanation for the long-run price drift post-going concern. © 2020 Informa UK Limited, trading as Taylor & Francis Group.
1 citations (Crossref) [2023-10-31] tex.ids: huangShortSellingPrior2020a tex.citation: https://api.elsevier.com/content/abstract/scopus_id/85097052844 type: Article
Keywords: dept.fin; peer-reviewed

The effect of political risk on shareholder value and the mitigating role of corporate social responsibility (CSR) - Chatjuthamard, Pattanaporn; Jiraporn, Pornsit; Sarajoti, Pattarake; Singh, Manohar (Managerial Finance, 2020)
Purpose: The study investigates the effect of political risk on shareholder value, using an event study and a novel measure of firm-level political risk recently developed by Hassan et al. (2017). In addition, the authors explore how corporate social responsibility (CSR) influences the effect of political risk on shareholder wealth. Design/methodology/approach: The authors exploit the guilty plea of Jack Abramoff, a well-known lobbyist, on January 3, 2006, as an exogenous shock that made lobbying less effective and less useful in the future, depriving firms of an important tool to reduce political exposure. Findings: The results show that the market reactions are significantly more negative for firms with more political exposure. Additional analysis corroborates the results, including propensity score matching, instrumental-variable analysis and Oster's (2019) method for testing coefficient stability. Finally, the authors note that the adverse effect of political risk on shareholder value is substantially mitigated for firms with strong social responsibility, consistent with the risk mitigation hypothesis. Originality/value: This study is the first to explore the effect of political risk on shareholder value using a novel measure. Furthermore, it is also the first to show that CSR alleviates the cost of political risk to shareholders. © 2020, Emerald Publishing Limited.
2 citations (Crossref) [2023-10-31] tex.ids: chatjuthamardEffectPoliticalRisk2020a tex.citation: https://api.elsevier.com/content/abstract/scopus_id/85086095623 type: Article
Keywords: CSR; Corporate social responsibility; Event study; Firm risk; G34; M14; Political risk; Shareholder wealth; dept.fin; dept.grad; peer-reviewed

The effect of relationship banking on firm efficiency and default risk - Yildirim, Alev (Journal of Corporate Finance, 2020)
Does relationship bank oversight reduce firm default risk and improve firm operational efficiency? I find that a new loan from a relationship bank reduces the default probability and increases the efficiency of a borrowing firm, benefiting both banks and borrowers. Moreover, inefficient and less creditworthy firms experience the highest reductions in their default risks and improvements in their efficiencies in the years following new relationship bank loans. Further, these benefits are disrupted when the relationship bank is acquired.
21 citations (Crossref) [2023-10-31] WOS:000602840200032
Keywords: Data envelopment analysis; Default risk; Firm efficiency; Relationship banking; Stochastic frontier analysis; Total factor productivity; dept.fin; peer-reviewed

Cohabitation before marriage: Do prior alliances enhance post-merger performance? - He, Zhaozhao; Yu, Han; Du, Lijing (Review of Quantitative Finance and Accounting, 2020)
We investigate the impact of prior alliance relationships on subsequent mergers between partner firms. We argue that an acquirer’s prior alliance experience with the target reduces information asymmetry, which helps improve acquisition performance. Alternatively, agency problems arising from familiarity may lead to inefficient decision making. Examining mergers between 1986 and 2014, we find evidence that prior alliance collaboration is positively associated with the acquirer’s long-term profitability and growth. This positive effect is more pronounced when target-specific learning and experience are more crucial to merger success, such as targets in knowledge-intensive or organizational-capital-intensive industries as well as cross-industry mergers. However, we cannot formally rule out the possibility that our results are partly driven by the small size of our sample.
4 citations (Crossref) [2023-10-31] tex.ids: heCohabitationMarriagePrior2019a, heCohabitationMarriagePrior2020 tex.citation: https://api.elsevier.com/content/abstract/scopus_id/85066470496 type: Article
Keywords: D80; G34; Information asymmetry; L14; L24; Learning and resources sharing; Mergers and acquisitions; O30; O32; Post-merger performance; Strategic alliance; dept.fin; peer-reviewed

The intra-industry effects of proxy contests - Chen, Fang; Huang, Jian; Yu, Han (Journal of Economics and Finance, 2020)
In this study, we examine the intra-industry effect of proxy contests. Proxy contests convey the information of common industrial risks or expected competitive relationship change. We find significant negative abnormal returns in the group of competitors of target firms with negative abnormal returns, and such negative abnormal returns become larger for similar-size competitors. In contrast, there are no significant abnormal returns for competitors of target firms with positive abnormal returns. These findings are consistent with the information-based theory but not the competitive theory. © 2019, Academy of Economics and Finance.
1 citations (Crossref) [2023-10-31] tex.ids: chenIntraindustryEffectsProxy2020, lens.org/134-505-396-626-539 tex.citation: https://api.elsevier.com/content/abstract/scopus_id/85070373506 tex.type: [object Object] type: Article
Keywords: Competitive effect; Information-based effect; Intra-industry effect; Proxy contest; dept.eco; dept.fin; peer-reviewed

CEO characteristics, firm performance, and corporate political contributions - Subrahmanyam, Vijaya; Singh, Manohar; Pennathur, Anita K. (Review of Financial Economics, 2020)
We investigate if CEO characteristics determine the choice of Political Action Committee (PAC) contributions by firms and if such participation leads to better firm performance. Using a unique, hand-collected database, we also focus on the identity of the politicians receiving PAC contributions to examine the impact of the value-relevance of such contributions. Examining data on corporate contributions made to candidates seeking federal office during the 2002, 2004, and 2006 election cycles, we find that CEO dominance and interest alignment influence strategic choices of firms with regards to establishing PACs. Our analysis of value-relevant contributions shows that firms prefer to donate to politicians representing the state of a firm's headquarters, validating the truth to the adage that all politics is local. However, these targeted political contributions do not have a discernible impact on firm performance.
2 citations (Crossref) [2023-10-31] tex.ids: lens.org/032-725-424-162-142, pop00254 tex.type: [object Object]
Keywords: CEO characteristics; CEO dominance; agency theory; corporate political contributions; dept.fin; dept.grad; firm performance; peer-reviewed